If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + (5q + -1w) = 0 Remove parenthesis around (5q + -1w) 1 + 5q + -1w = 0 Solving 1 + 5q + -1w = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 5q + -1 + -1w = 0 + -1 Reorder the terms: 1 + -1 + 5q + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5q + -1w = 0 + -1 5q + -1w = 0 + -1 Combine like terms: 0 + -1 = -1 5q + -1w = -1 Add 'w' to each side of the equation. 5q + -1w + w = -1 + w Combine like terms: -1w + w = 0 5q + 0 = -1 + w 5q = -1 + w Divide each side by '5'. q = -0.2 + 0.2w Simplifying q = -0.2 + 0.2w
| V-(3n+x)= | | 7p-26=107 | | 6-4(x-3)=2x-1 | | x=-2y-7 | | -.2(3+a)=-4 | | (3x-2w)-q= | | X(x-12)+15=-4x | | 16c^4+12b^3=0 | | Y=3/4•9/2 | | 12x+12=-9x+15-4x | | y= 0.05 x + 25 | | 12x+12=-3x+15-4x | | 5v-10/v-6=5/2 | | 35z+4(7z-42)=18(2z-3) | | f(x)=-5+2 | | 5-r/r-6=5/8 | | 10-(2n+v)= | | a=4a | | 2.23+x=5.84 | | (2q+r)= | | x=80000*(1+1.4)100 | | -(r+n+t)= | | (N-t)+4= | | -20=x/-4 | | x^2+9y^2-8x+7=0 | | 5*(2X+4)=303 | | (R+n)-7= | | 10+y=0 | | y=17.6+1.2(1+1r) | | 5+(3-n)= | | 5x+1=81x | | y=17.6+1.2r(1+1t) |